Published financial statements in Singapore : correlation with the auditor? - Pang, Seng Chyi (2015)
This study aims to investigate, in Singapore context, the relationship between certain aspects of published financial statements and the auditor. The aspects of financial statements studies are Voluntary Disclosure, Accounting Policies and Form and Presentation of the financial statements. Chi-square tests were performed on the sample collected. Results indicate that generally there is no significant correlation between these aspects of financial statements and the auditor. However, in the Form and Presentation, the auditor does have an influence on areas like the titles and the format of the financial statements.